Kesalahan Berbahasa Lisan Penutur BIPA dalam Kanal YouTube “Sarah Johnson” (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to examine the language errors made by BIPA speakers on Sarah Johnson's YouTube channel. The method used is descriptive qualitative method. Data collection was carried out by looking at two videos on Sara Johnson's YouTube channel and then transcribing the recordings into writing. The analysis are carried out by reducing data, presenting data, and concluding research results. The aims of this research are (1) to describe errors in Indonesian pronunciation. In Indonesian pronunciation errors, 3 types of errors were found caused by phoneme changes, 2 forms of errors caused by adding and subtracting phonemes, and 2 forms of errors caused by pausing errors; (2) describe errors in the formation of Indonesian words. In the errors in the formation of Indonesian words, 6 forms of errors were found in the use of affixes, and 4 forms of errors in the choice of words; (3) errors in sentence construction in Indonesian. In the errors in the preparation of Indonesian sentences, 1 form of language error was found which was caused by ambiguity in the sentence, so that overall 18 forms of Indonesian language errors were found in this study. Errors in spoken language on the YouTube account "Sarah Johnson" are caused by errors or errors experienced by Sarah Johnson. This error is also caused by the influence of the mother tongue (interlingual) and also the lack of understanding and complexity of the second language that is less mastered (intralingual).